Phaenocarpa ruficeps Nees 1811 ... - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Phaenocarpa ruficeps (Nees, 1811) Distribution in Iran. Khorasan (Ghahari et al. 2011a; Khajeh et al. 2014). Distribution outside Iran. Widely distributed for northern, western, central and eastern Europe to Rusia (Fischer 1993a). Armenia, Belgium, Bulgaria, Canada, China, Finland, France, Iceland, Italy, Korea, Madeira Islands, Moldova, Mongolia, Morocco, South Africa, Tunisia, Uzbekistan and former Yugoslavia (Yu et al. 2012), Austria, Germany, Poland, Romania, Sweden, Switzerland and former USSR (Fischer 1973a; Yu et al. 2012), Bosnia-Herzegovina and Serbia (Papp 2009b; Yu et al. 2012), Czech Republic (Lozan et al. 2010; Yu et al. 2012), Greece (Papp 2007a; Yu et al. 2012), Hungary (Fischer 1973a; Papp 2008; Yu et al. 2012), Kazakhstan, Russia and USA (Shenefelt 1974; Tobias 1986b; Belokobylskij and Tobias 1997; Yu et al. 2012), Madeira Islands (van Achterberg and Aguiar 2009), Netherlands (van Achterberg 1988; Yu et al. 2012), Spain (Docavo et al. 1985; Fischer et al. 2008; Yu et al. 2012), United ... : Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on page 7, DOI: 10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961 ...